The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1021/acs.chemmater.2c02018
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Isomerization of Magic-Sized Inorganic Clusters Chemically Driven by Atomic-Bond Exchanges

Abstract: The recent discovery of chemically reversible isomerization of CdS clusters (Williamson et al. Science2019, 363, 731) shows that the structural transformation of such inorganic clusters has essential characteristics of both small-molecule isomerization and solid−solid transformation. Despite its importance in synthesizing colloidal quantum dots from cluster intermediates (so-called "magic-sized clusters" or MSCs), the underlying mechanism for such inorganic isomerization is not yet understood. Here, using ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…In contrast, in terms of energetics (Figure c), the liberation of Cd­(O 2 CR) 2 cannot promote the BX defect formation in the CdS cluster because of the different nature of the ligand network in the group II–VI cluster (see discussion in Section ). Instead, our previous DFT study showed that it is possible to chemically induce multiple Cd–S bond exchanges in a single Cd 41 S 20 cluster by using methanol adsorption on the cluster (Figure b). The multiple bond exchanges then lead to the wurtzite-to-zincblende transition of the partially ordered Cd 41 S 20 core rather than creating substantial structural disruption (e.g., rupture) on the cluster surface.…”
Section: Results and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In contrast, in terms of energetics (Figure c), the liberation of Cd­(O 2 CR) 2 cannot promote the BX defect formation in the CdS cluster because of the different nature of the ligand network in the group II–VI cluster (see discussion in Section ). Instead, our previous DFT study showed that it is possible to chemically induce multiple Cd–S bond exchanges in a single Cd 41 S 20 cluster by using methanol adsorption on the cluster (Figure b). The multiple bond exchanges then lead to the wurtzite-to-zincblende transition of the partially ordered Cd 41 S 20 core rather than creating substantial structural disruption (e.g., rupture) on the cluster surface.…”
Section: Results and Discussionmentioning
confidence: 98%
“…In contrast, when it comes to the same α-to-β isomerization of Cd 37−N* S 20 (O 2 CH) 34−2N* , the Cd−S bond exchange requires only local ligand rearrangement around the defect site. Recently, we proposed a Cd 41 S 20 cluster 50 to elucidate the multiscale nature of the chemically reversible isomerization observed in CdS MSC 51 (see also Section 3.6 for more discussion). However, for a more direct comparison with the case of In 37−N* P 20 (O 2 CH) 51−3N* , we here adopted the core structures of αand β-In 2c); that is, in terms of energetics, the liberation of Cd(O 2 CR) 2 cannot promote the BX defect formation in the CdS cluster.…”
Section: Mechanism For Thermal Destabilization Of the Inp Mscmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Cd 13 S 13 (1878 Da based on MS), 27 Cd 37 S 20 (4245 Da based on In 37 P 20 ), 10,28 and Cd 41 S 20 (based on calculation) are claimed. 29 Figure S5-2 shows the lower mass region (from 1500 to 5000 Da) of MALDI-TOF MS for MSC-322 and MSC-360; no mass peaks are detected at 1878 and 4245 Da. MSC-345 is seen when MSC-322 is diluted in CH (Figure S2-3) or in a mixture of CH and OTA (Figures 3 and 4) at room temperature; we are not able to prepare a MS sample for MSC-345.…”
mentioning
confidence: 99%
“…In this study, the wurtzite Cd 37 S 20 cluster structure is utilized, which is widely accepted as one of the most representative models for these clusters. , To simplify the model, we used acetate ions to represent the experimental oleate ligands. Excess ligands were initially placed near the semiconductor core to replicate the ligand-rich environment of the experiments, followed by geometry optimization using DFT with the PBE functional .…”
mentioning
confidence: 99%